ANALISIS EFEKTIVITAS PENGELOLAAN DANA DESA (KAJIAN IMPLEMENTASI DAN REALISASI DANA DESA, DESA CANDRA JAYA, MERAUKE) - Parman, Parman; Ismail, Ismail; TPM Djanggo, Romualdus; Aji Wijaya, Wahyu; N. Lutfiah, Mirfa (Ekonomi Syariah STAI Sangatta Kutai Timur, 2025)
The main purpose of village fund management is to support village development, economic empowerment and the implementation of village government. The expected output is the realization of a strong, independent and prosperous village. This research focuses on three main aspects, namely the planning of Village Fund expenditure, the effectiveness of the use of Village Fund, and the impact of Village Fund expenditure on community welfare which includes the fields of income, education, health, and infrastructure. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation, and uses interactive data analysis which includes data reduction, data presentation, and conclusion drawn. The findings show that the management of the Village Fund has been running effectively and in accordance with the work plan, with the realization of the budget reaching 100% every year. The Village Fund has a positive impact on improving community welfare, especially through infrastructure development, improving education and health services, and community empowerment. However, the productive economic empowerment program still needs to be improved so that the benefits of the Village Fund can be felt more evenly and sustainably.